New records of Noctuinae for Iran with additional distribution data (Lepidoptera: Noctuidae) - S. Shahreyari-Nedja; M. Esfandari; A. Rasekh; M. S. Mossadegh; A. Shirvani (SHILAP)
Numerous expeditions have been done in Iran during more than 150 years to investigate the Noctuidae fauna. However, still white patches remain to be extensively explored. In this study, night samplings performed by light traps at different Iranian provinces to study some tribes of Noctuinae. Here, we present 43 species and subspecies, among them three species of Dasypolia eberti Boursin, 1967, Episema minutoides Ronkay, Varga & Hreblay, 1999 and Polymixis schistochlora Ronkay, Varga & Hreblay, 1998 are newly reported for the fauna of Iran. Twenty-six of identified taxa are new records for one or more provinces of Iran. Adults and genitalia of new records for Iran are illustrated with notes on their bionomy and identification.